Comparative analysis of gut fungal composition and structure of the yaks under different feeding models - Zhu, Yanbin; Cidan, Yangji; Sun, Guangming; Li, Xin; Shahid, Muhammad Akbar; Luosang, Zhaxi; Suolang, Zhaxi; Suo, Lang; Basang, Wangdui (Frontiers in Veterinary Science, 2023)
Yaks inhabiting the Qinghai-Tibet Plateau is a rare breed, which is closely related to local economic development and human civilization. This ancient breed may have evolved unique gut microbiota due to the high-altitude hypoxic environment. Gut microbiota are susceptible to external factors, but studies regarding the effects of different feeding models on gut fungal community in yaks remains scarce. In this study, we compared and analyzed the composition and variability of gut fungal community among wild yaks, house-feeding domestic yaks and grazing domestic yaks. Results revealed that Basidiomycota and Ascomycota were the most preponderant phyla in the gut bacterial community regardless of feeding models. Moreover, although the types of dominant fungal phyla did not change, their abundance changed significantly. Intergroup analysis of of microbial diversity demonstrated that the Shannon and Simpson indices of wild yaks and grazing domestic yaks were significantly higher than those of house-feeding domestic yaks. Fungal taxonomic analysis showed that there were 20 genera that were significantly different between the wild yaks and grazing domestic yaks and 16 genera were significantly different between wild yaks and house-feeding domestic yaks. Additionally, the proportions of 14 genera observably decreased, whereas the proportions of 8 genera observably increased in house-feeding domestic yaks as compared to grazing domestic yaks. Taken together, this study showed that the composition and structure of gut fungal community differ significantly between yaks raised in different breeding groups. Furthermore, this survey also contributes to understanding the characteristics of the gut fungal community of yaks between different feeding models and raising public concern about gut fungal community.